Mode-locking using right-angle waveguide, based nanotube saturable absorber - Brown,G; Thomson,RR; Beecher,SJ; Mary,R; Popa,D; Sun,Z; Torrisi,F; Hasan,T; Milana,S; Bonaccorso,F; Ferrari,AC; Kar,AK (Pacific Rim Conference on Lasers and Electro-Optics, CLEO - Technical Digest, 2013)
We report passive mode-locking of an Er-doped fiber laser using carbon nanotubes deposited on the facet of a right-angle optical waveguide. © 2013 IEEE.